Diagnóstico de las debilidades de la estructura de la red inalámbrica del gad del cantón Montalvo - Jimenez Sanchez, Jefferson Francisco (2019)
In Ecuador, the massive increase in wireless networks is evident, because this type of network plays a very important role today because of its functionality, which is to allow wireless connectivity to electronic devices in an easy, fast and easy way. Once the information shared between them. The present study was conducted in the Decentralized Autonomous Government of the Montalvo Canton. The research methodology used for the development of the case study was the qualitative one, in addition, its techniques and instruments were used to gather information. For the diagnosis of the weaknesses of the wireless network of the GAD, the following tools were used such as Linset, Wifimosys, Commview for Wi-Fi, Aircrack-ng and Wifislax